2022
DOI: 10.2196/40340
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Parental Factors of Adolescents’ mHealth App Use: Nationally Representative Cross-sectional Study

Abstract: Background Knowledge of the characteristics of adolescents who use mobile health (mHealth) apps to monitor health and how these characteristics differ from those of app nonusers is limited. Objective We aimed to determine mHealth app use based on adolescent and parental factors, including sociodemographics, digital skills, and health indicators, in a nationally representative sample of Czech adolescents (N=2500). Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…For example, female adolescents have been shown to be more willing to report symptoms after concussion [ 33 ] and with greater frequency [ 6 ]. Particularly in digital use, female adolescents were found to have stronger motives for interpersonal communication and self-expression than male adolescents [ 34 35 ], which may explain why higher response rates were observed in female adolescents while using the mHealth app in this study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, female adolescents have been shown to be more willing to report symptoms after concussion [ 33 ] and with greater frequency [ 6 ]. Particularly in digital use, female adolescents were found to have stronger motives for interpersonal communication and self-expression than male adolescents [ 34 35 ], which may explain why higher response rates were observed in female adolescents while using the mHealth app in this study.…”
Section: Discussionmentioning
confidence: 99%
“…These skills, triangulation and fact-checking sources, are not captured in the current eHEALS and may be useful to assess in addition to, or in a revised version of, the eHEALS. Given that adolescents use health-related mobile applications to monitor their health behavior (Gulec & Smahel, 2022; Wartella et al, 2016), a revised version of the eHEALS should also assess eHL skills associated with the navigation and application of health information from mobile applications. These expansions in the assessment of eHL skills may address the ceiling effect problem of the eHEALS.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a meta-analysis by Kim et al (2023) found a moderate correlation between eHL and several health behaviors. Among adolescents, higher eHL skills have been associated with nutrition, stress management, and exercise behaviors (Korkmaz Aslan et al, 2021) as well as higher frequency of using mHealth apps (e.g., apps to track calorie intake/expenditure; Gulec & Smahel, 2022). Low eHL has been linked to lower likelihood of online information-seeking in adolescents (Chang et al, 2015; Ghaddar et al, 2012).…”
Section: Ehealth Literacymentioning
confidence: 99%
“…These would help the users know their health status, namely health awareness. 34 The BeWS-SPA program uses a notification system to encourage users to assess their daily stress levels. In addition, the researchers developed this app by considering the limitations or related problems in the app functions in a previous study and adjusting for better functions.…”
Section: Discussionmentioning
confidence: 99%